Beyond test performance: a broader view of stereotype threat. (October 2016) - Lewis, Neil A.; Sekaquaptewa, Denise
Highlights: Stereotype threat arises when a negative stereotype about one's group seems to apply. We review research on threat outcomes beyond the traditional focus on test scores. Threat antecedents include environmental cues and consequences include well-being. Interventions should go beyond test scores, for example, targeting intergroup interaction. Abstract : Stereotype threat is the 'social psychological threat that arises when one is in a situation or doing something for which a negative stereotype about one's group applies' [1 ]. Although much of the research on stereotype threat has focused on how stereotype threat affects test performance, its original conception described a broader and more general phenomenon. In this article we review stereotype threat research, taking a broader view on threat beyond the realm of test performance, focusing on its antecedents (e.g., environmental stereotype cues) and consequences (e.g., effects on interracial interaction). Interventions have also focused primarily on improving or preserving test performance, indicating the need for interventions that address the broader consequences of threat.